Mensuração do grau de inovação em empresas de energia, petróleo e gás da cidade de Mossoró-RN - Morais, Amanda Queiroz de (Universidade Federal Rural do Semi-Árido, 2019)
Innovation is recognized as the solution of the needs in optimizing processes, improving products, conquering new markets and keeping pace with changes in the scenario in which the company is inserted. With the new needs that arise and the economic influence, innovation becomes the essence of entrepreneurship and the objective by which companies invest in research and development, for the development of new processes / products, seeking to follow the technological advances. This research aims to measure the degree of innovation in energy, oil and gas companies in the city of Mossoró-RN, classified as descriptive and quantitative. A survey was carried out in these companies, which consisted of a questionnaire of 13 dimensions. As a result, the general average of the companies was 4.29, which classify them as innovative methodical, in face of a scale that has a variation between 1 and 5, showing the assiduity of the companies to innovate.
Monografia
Keywords: Inovação; Grau de inovação; Petróleo e gás; Energia; Innovation; Degree of innovation; Oil and gas; Energy; ENGENHARIAS::ENGENHARIA DE PRODUCAO